Physical Activity Levels and Their Associations With Postural Control in the First Year After Stroke. Issue 9 (1st September 2016) - Persson, Carina U.; Hansson, Per-Olof; Lappas, Georgios; Danielsson, Anna
Abstract: Background: There is limited research concerning the physical activity levels over time of people who have survived stroke. Objective: The study objectives were: (1) to describe self-reported physical activity levels at 3, 6, and 12 months after stroke onset and (2) to analyze whether there was an association between self-reported physical activity level and postural control. Design: This was an observational and longitudinal study. Methods: Ninety-six participants with a first-ever stroke were assessed for self-reported physical activity levels with the Physical Activity Scale for the Elderly (PASE) in the first year after stroke. Postural control also was assessed with the modified version of the Postural Assessment Scale for Stroke Patients (SwePASS). Results: The raw median PASE scores at 3, 6, and 12 months after stroke were 59.5, 77.5, and 63.5, respectively. The model-estimated relative changes in mean PASE scores (as percentages) followed the same pattern, independent of age, sex, and SwePASS scores. Between 3 and 6 months after stroke, PASE scores increased by 32%, with no significant change between 3 and 12 months and between 6 and 12 months after stroke. For each unit increase in the SwePASS score at baseline, there was a 13% increase in the PASE score during follow-up. Limitations: The sample size was limited. Although the PASE is based on the metabolic equivalent of the task, the actual physiological intensity of a person's performance of the activities is unknown. Conclusions: Self-reported physical activity levels were low in the first year after stroke. Good postural control in the first week after stroke onset was positively correlated with higher levels of self-reported physical activity in the first year after stroke.